From Research to Practice: Towards an Integrated and Comprehensive Faculty Development Program - Lawrence C. Ragan; Paula Mae Bigatel; Shannon S. Kennan; Janet May Dillon (Online Learning, 2012)
This article describes the design and development of a professional development program based upon research on the competencies necessary for online teaching success [1] conducted at Penn State University in 2009-2010. The article highlights how the results of this research are being aligned with various professional development courses comprising the certificate program for online faculty at Penn State’s World Campus. This article describes the process of research design and implementation to the direct application for professional development.